2014
DOI: 10.1186/s40543-014-0022-5
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characterization of in vitro interactions of cetirizine and NSAIDS

Abstract: Background: Cetirizine (anti-allergy agent) and non-steroidal anti-inflammatory drugs (NSAIDs; anti-inflammatory agents) are co-administered drugs. Cetirizine, a P-glycopretein substrate may be affected by the use of NSAIDs. In the present work, quantification of cetirizine in the presence of commonly co-administered NSAIDs such as diclofenac sodium, ibuprofen, flurbiprofen, tiaprofenac acid, meloxicam and mefenamic acid were studied using the RP-HPLC technique. Methods: A high-throughput HPLC method for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A very weak singlet was present at 10.6 ppm for the one proton of the carboxylic acid group. 33 Some characteristic peaks of LCD were found also in the spectra of nanoparticle formulations, indicating successful incorporation of drug into the nanoparticles with no chemical changes. 34 The data were also supported by the DSC and FT-IR results.…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 95%
“…A very weak singlet was present at 10.6 ppm for the one proton of the carboxylic acid group. 33 Some characteristic peaks of LCD were found also in the spectra of nanoparticle formulations, indicating successful incorporation of drug into the nanoparticles with no chemical changes. 34 The data were also supported by the DSC and FT-IR results.…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 95%
“…Reported methods were utilized for interaction (Arayne et al, 2008(Arayne et al, , 2010cMirza et al, 2013a;Shamshad et al, 2014). Briefly, in each set of experiment, pioglitazone tablet was added into the dissolution medium along with fexofenadine, cetirizine or levocetirizine tablets at zero minute.…”
Section: Interaction Studiesmentioning
confidence: 99%
“…In vitro techniques offer a complete means to create a huge amount of data using minimum resources. Investigation of in vitro drug interactions has also been reported by using minimum standards (Arayne et al, 2008(Arayne et al, , 2010cMirza et al, 2013b;Shamshad et al, 2014). These suggested that in vitro approaches should be properly characterized; validated and proper controls should be incorporated in routine use.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the number of HPLC methods has been reported for the determination of cetirizine in the presence of several other drugs as pseudoephedrine [16], chloroquine and pyrimethamine [17], hydroxyzine [18], H 2 receptor antagonists [19], statins [20], with different antihistamine [21], calcium-channel blockers [22], and NSAIDs [23]. However, no method for the simultaneous determination of cetirizine in the presence of quinolones was reported.…”
Section: Introductionmentioning
confidence: 99%